Thirty‐day postoperative mortality for endometrial carcinoma in England: a population‐based study. (29th February 2016) - Gildea, C; Nordin, A; Hirschowitz, L; Poole, J
Abstract : Objective: To quantify trends in 30‐day mortality following surgery for endometrial carcinoma in England, and investigate hospital‐ and geographical‐level variations. Design: Retrospective population‐based observational study using cancer registration and Hospital Episodes Statistics data. Setting: England. Population: Women diagnosed with endometrial carcinoma (ICD10 C54‐C55 excluding sarcomas and malignant mixed Mullerian tumours) between 2000 and 2009 who were treated surgically ( n  = 38 332). Methods: Random effects logistic regression model of postoperative mortality rates, adjusting for patient‐ and/or tumour‐level factors (namely age, income deprivation, year of diagnosis, FIGO stage and grade). Case‐mix adjusted postoperative mortality rates for hospitals and cancer networks were derived from the model. Multiple imputation was used to account for missing stage and grade data. Main outcome measures: 30‐day postoperative mortality rate. Results: For 2000–2009, the percentage of women dying within 30 days of surgery for endometrial carcinoma was very low at 0.61% (235 deaths), and decreased from 0.70% in 2000–2001 to 0.48% in 2008–2009. Postoperative mortality rates were lower for laparoscopic surgery, and higher for older women, those with advanced stage disease and high‐grade tumours. Crude and case‐mix adjusted results indicated that one hospital had a higher postoperative mortality rate than expected. Conclusions: The postoperative mortality rate for endometrial carcinoma in England is low and has improved since 2000, with increasing use of laparoscopic surgery. Postoperative mortality rates differed by surgical approach, patient age, disease stage and tumour grade. Only one hospital had a higher postoperative mortality rate than expected after adjusting for patient case‐mix. Tweetable abstract: More women with endometrial cancer but better 30‐day survival after surgery since 2000. Tweetable abstract: More women with endometrial cancer but better 30‐day survival after surgery since 2000.